Draba dongchuanensis (Brassicaceae), a new species from Yunnan, China - Al-Shehbaz, Ihsan A.; Yue, Ji-Pei; Deng, Tao; Chen, Hong-Liang (Phytotaxa, 2014)
Draba dongchuanensis is described, illustrated, and compared with several, primarily Himalayan and Tibetan species, including D. amplexicaulis, D. draboides, D. mongolica, D. polyphylla, D. setosa, and D. surculosa. From these, it is readily distinguished from all of the Himalayan species of Draba by a combination of strongly dilated filament bases, setose basal leaves, and auriculate middle cauline leaves.